Beyond the global motion deficit hypothesis of developmental dyslexia: A cross-sectional study of visual, cognitive, and socio-economic factors influencing reading ability in children. (June 2019) - Piotrowska, Barbara; Willis, Alexandra
Abstract: Although primarily conceptualized as a disorder of phonological awareness, developmental dyslexia is often associated with broader problems perceiving and attending to transient or rapidly-moving visual stimuli. However, the extent to which such visual deficits represent the cause or the consequence of dyslexia remains contentious, and very little research has examined the relative contributions of phonological, visual, and other variables to reading performance more broadly. We measured visual sensitivity to global motion (GM) and global form (GF), performance on various language and other cognitive tasks believed to be compromised in dyslexia (phonological awareness, processing speed, and working memory), together with a range of social and demographic variables often omitted in previous research, such as age, gender, non-verbal intelligence, and socio-economic status in an unselected sample ( n  = 132) of children aged 6–11.5 yrs from two different primary schools in Edinburgh, UK. We found that: (i) Mean GM sensitivity (but not GF) was significantly lower in poor readers (medium effect size); (ii) GM sensitivity accounted for only 3% of the variance in reading scores; (iii) GM sensitivity deficits were observed in only 16% of poor readers; (iv) the best predictors of reading performance were phonological awareness, non-verbal intelligence, and socio-economic status, suggesting the importance of controlling for these in future studies of vision and reading. These findings suggest that developmental dyslexia is unlikely to represent a single category of neurodevelopmental disorder underpinned by lower-level deficits in visual motion processing.